Field compaction control by way of correlation between elasticity module and layer rigidity with moisture content - Fernandes,Daniel Pinto (2019)
Abstract The present research had as its basic objective to contribute with the improvement in the quality control evaluation of the compacting process in road works. The real contribution of the survey is to establish an innovative way of controlling the compaction process in the field, with employment of the Humidity versus Rigidity and the Humidity versus Elasticity Module curves, turning the methodology faster and more efficient than the conventional procedures. In fact, to date, the compacting control procedures contemplate methods that are inaccurate and limited by several constraints, rendering the technique unfeasible and time consuming, in detriment of the work schedule. Thus, this study proposes to define a rational correlation criterion between the geotechnical characterization with results obtained in the laboratory using conventional methods and the elastic parameters obtained by applying the rigidity meter of compacted soils, based on a statistical treatment of data concerning the infrastructure of experimental road and railway sections. The results obtained in the research were the correlation curves for Humidity versus Rigidity, and for Humidity versus Elasticity Module, for the material of the deposit, with the corresponding equations. Thenceforth, with the correlation curves, it will be much easier to obtain the moisture content that the soil requires on the earthworks. By measuring the modulus of elasticity or rigidity through the stiffness meter of compacted soils, the respective curve checks if the value of the soil moisture content is compatible with the variation of the moisture content in the project.